1983
DOI: 10.1093/nar/11.17.6021
|View full text |Cite
|
Sign up to set email alerts
|

Construction and characterization of type II collagen complementary deoxyribonucleic acid dones

Abstract: The mRNA for type II collagen was purified from embryonic chick sternum or from purified sternal chondrocytes with guanidine thiocyanate as the extractant. Double-stranded cDNAs to procollagen mRNAs from sternum were synthesized and dC-tailed. After annealing with PstI-cleaved, dG-tailed pBR322, this DNA was used to transform Escherichia coli X1776. Transformed colonies were screened by colony hybridization to type I and II collagen cDNAs. Clones that preferentially hybridized to type II cDNA were characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
15
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…1). A very prominent RNA of 5,100 bases was detected in normal chondrocytes, as described previously (16,28,57). Transformed chondrocytes displayed reductions in this RNA species to 1.5% (wt-RSV-transformed cells) and 3% (ts-RSVtransformed cells) of normal levels, consistent with the dramatic reduction in the rate of type II collagen synthesis in these cells (2).…”
supporting
confidence: 75%
See 3 more Smart Citations
“…1). A very prominent RNA of 5,100 bases was detected in normal chondrocytes, as described previously (16,28,57). Transformed chondrocytes displayed reductions in this RNA species to 1.5% (wt-RSV-transformed cells) and 3% (ts-RSVtransformed cells) of normal levels, consistent with the dramatic reduction in the rate of type II collagen synthesis in these cells (2).…”
supporting
confidence: 75%
“…The type II collagen gene does not possess an inverted repeat sequence in the translation initiation region (21) and does not possess multiple consensus signals for polyadenylation (35,44). Furthermore, although there is one report of multiple type II collagen RNAs (57), recent reports from other laboratories have not shown this (16,21,28,65).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Gerstenfeld et al (18) have shown that quantitative separation of RNA from DNA can be achieved by using this modification of the original GuHCl RNA isolation procedure (12). We found this method to give greater yields of intact mRNA despite previous reports which suggested that the GuSCN method (12) was more efficient for extraction of RNA from chondrocytes (31). Polyadenylated mRNA was prepared by the method of Tate et al (47).…”
mentioning
confidence: 79%